Cholesteric Liquid Crystal Materials for Tunable Diffractive Optics. Issue 15 (3rd June 2018) - Ryabchun, Alexander; Bobrovsky, Alexey
Abstract: Modern optics and photonics constantly require break‐through materials and designs in order to achieve miniature, lightweight, highly tunable, and effective optical devices. One of the basic optical components is the diffraction grating (DG), widely used for the dispersion of light, beam steering, etc. This review gathers research efforts on diffractive optical elements based on cholesteric liquid crystal (CLC) materials with a supramolecular helical architecture. All main types and fabrication approaches of periodic diffractive structures from CLCs are classified and described. Key optical properties of DGs, their advantages and drawbacks are considered. Special attention is paid on the tunability of DGs including design principles and prospective chiral materials. The review consists of three parts divided according to the formation mechanism of diffractive structures: i) the spontaneously formed periodic structures from CLCs confined in cells with hybrid or homeotropic boundary conditions; ii) DGs generated by external electric field applied to CLCs layers; iii) light‐generated DGs (e.g., obtained by holography, mask exposure, photoalignment). The review also aims to initiate and gain collaborations between physicists, engineers and organic chemists to combine novel chiral photoswitches and molecular motors with sophisticated optical design paving the way towards novel smart optical materials. Abstract : Cholesteric materials possessing supramolecular helical architecture are a field of great interest for tunable diffractive optics. The review gathers research efforts on smart organic optics from cholesteric liquid crystals. Main types and fabrication approaches of diffractive structures are classified and described. Special attention is paid to the electro‐ and phototunability of optical elements including basic design principles and perspective chiral materials such as photoswitches and molecular motors.